Stress-Cultural Democracy Da'wah at the Mosque - Syarifudin Syarifudin; Baiti Ren; Fitri Fitri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2020)
This study examines the collision of democratic systems through the election of village heads and the process of the resilience of cultural da'wah at mosques, which has an impact on the weakening of dakwah in Kampung Baru and Lonthor Banda Neira villages. The issue of the discussion examines the da'wah experience of mosque administrators regarding the encounter of democracy through the process of cultural da'wah at the mosque. This research uses a case study method with a qualitative approach. Data collection techniques through observation, interviews, and focus discussion groups. This study's results indicate that the adaptation of a democratic culture through village head elections occurs cultural stress between mosque administrators who maintain the resilience of the dakwah culture with a democratic system through the voting of the village head in Banda Neira. The cultural stress process goes through three stages: the cultural meeting stage, cultural clash action, cultural assimilation, and artistic collaboration. Due to social stress, social reality creates a feeling of shame, underappreciation, and a weakening of the solidarity of mosque administrators. Penelitian ini mengkaji benturan sistem demokrasi melalui pemilihan kepala desa dan proses ketahanan dakwah kultural pada masjid, yang berdampak terhadap pelemahan dakwah di desa Kampung baru dan Lonthor Banda Neira. Isu pembahasannya mengkaji pengalaman dakwah pengurus masjid terhadap perjumpaan demokrasi melalui proses dakwah kultural di Masjid. Penelitian ini menggunakan metode studi kasus dengan pendekatan kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan focus discussion group. Hasil penelitian ini menunjukkan bahwa adabtasi budaya demokrasi melalui pemilihan kepala desa terjadi stress cultural antara pengurus masjid yang menjaga ketahanan cultural dakwah dengan sistem demokrasi melalui pemilihan kepala Desa di Banda Neira. Proses stress cultural melalui tiga tahap yakni; tahap meeting cultural, aksi benturan cultural, cultural asimilation, dan collaboration cultural. Realitas sosial akibat stress cultural memunculkan rasa malu, kurang dihargai, dan melemahnya solodaritas pengurus masjid.